Samples in Psychological Research – Conclusions and Recommendations from the Literature Review - Świderska, Joanna; Puchalska, Magdalena; Grzegorczyk, Maciej; Szałek, Zuzanna; Nadolna, Natalia; Andryszkiewicz, Martyna; Jastrzębska, Maria; Szablowski, Przemysław; Śmigrodzka, Maja (Przegląd Psychologiczny, 2023)
Objective: The goal of the review was to identify the elements occurring in the both survey procedure and sample descriptions and to formulate recommendations for the authors on this basis. Method: The study was conducted following the PRISMA standard. A total of 305 articles by Polish researchers from four journals were analyzed. Critical evaluation have been conducted for 230 articles of the analyzed sample, encompassing 295 research descriptions. Results: Analysis revealed that researchers most frequently report the research procedure, sampling method, sample size, form of the research and sociodemographic characteristics, such as: gender or sex and age. Conclusions: The conclusions drawn from the analysis and insights gained from the review led to the formulating recommendations regarding comprehensive methodological description of research procedures and samples.